1994
DOI: 10.1002/eji.1830241024
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of exogenous antigens by macrophages: analysis of major histocompatibility complex class I and II presentation and regulation by cytokines

Abstract: There is an antigen presenting cell (APC) in the lymphoid organs capable of presenting exogenous antigen (Ag) with major histocompatibility complex (MHC) class I molecules. This study was initiated to isolate clones of these APC to definitively establish their phenotype and to further study their properties. Murine bone marrow macrophages (BM M psi) were immortalized by overexpression myc and raf oncogenes. Five BM M psi cell lines were generated that are phagocytic and expressed at their surface M psi differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In general, VLPs have the potential to activate both endogenous and exogenous antigen pathways leading to the presentation of viral peptides by MHC class I and class II molecules [36]. In this study, we showed that anti-HA specific CD8+ T cells were elicited by a seasonal influenza VLP vaccine indicating that a multi-epitope vaccine is more likely than an inactivated, split vaccine to generate a broad-based immune response.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In general, VLPs have the potential to activate both endogenous and exogenous antigen pathways leading to the presentation of viral peptides by MHC class I and class II molecules [36]. In this study, we showed that anti-HA specific CD8+ T cells were elicited by a seasonal influenza VLP vaccine indicating that a multi-epitope vaccine is more likely than an inactivated, split vaccine to generate a broad-based immune response.…”
Section: Discussionmentioning
confidence: 70%
“…These viral proteins can be processed and presented on MHC class I molecules, therefore promoting presentation to T-cells by professional antigen presenting cells. In addition, cell-free VLPs bound with antibodies could be taken up by phagocytic cells via Fc receptors, thus increasing MHC class II presentation [36]. Antigens expressed in their native three-dimensional conformational form can elicit more effective antibody responses compared to proteins in their non-native forms [37].…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines BMC-2 and BMA macrophage cells [12] and DC2.4 dendritic cells [13] supplemented with 5% fetal calf serum (FCS). Stable HEK-TLR cells were obtained by calcium phosphate transfection of a pCDNA3 expession vector for a specific chimeric TLR with an in frame C-terminal YFP and selection in 0.4μg/ml G418.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we show that TLR ligands zymosan A (TLR-2), poly I:C (TLR-3) and LPS (TLR-4) induced sialidase activity on the cell surface of live BMC-2 macrophage [12] and DC2.4 dendritic [13] cells in culture after 2 min. This activity was revealed by a fluorescence (λem 450 nm) surrounding the cells treated with the fluorogenic sialidase substrate, 4MU-NeuAc (2′-(4-methylumbelliferyl)-α-N-acetylneuraminic acid) and caused by the emission of 4-methylumbelliferone (Fig.…”
Section: Sialidase Activity Associated With Tlr Ligand Treated Live Pmentioning
confidence: 99%
“…More specifically, the A3.1A7 macrophage cell line has been shown to present the immunodominant epitope of chicken ovalbumin, SIINFEKL, in association with the H-2K b MHC class I molecule (15). As previously demonstrated, when this antigenpresenting cell (APC) line is pulsed with SIINFEKL and then incubated with the T cell hybridoma RF33.70, IL-2 is produced by the RF33.70 T cell hybridoma at levels proportional to the number of H-2K b :SIINFEKL complexes expressed on the surface of the pulsed APCs (16).…”
Section: Assay For Macrophage Mhc Class I Presentation Of Epitope Pepmentioning
confidence: 99%